Physiotherapy Management of Medial Collateral Ligament (MCL) Repair: A Case Study - Dewanto, Adetya Priyo; Purwatama, Galeh; Zena, Dimas; Maghfiroh, Rinna Ainul (Academic Physiotherapy Conference Proceeding, 2023)
Introduction: The Medial Collateral Ligament (MCL) is a ligament located inside the knee joint that connects the femur to the tibia on the inner or medial side. The MCL's major role is to keep the knee joint stable and to avoid excessive sideways or valgus movements. Injury to the MCL might caused by valgus forces and sudden rotational extension of the knee, which frequently occurs during athletic activities causing the knee to be in a rotational position when the force is applied. As a result, the MCL is sprained or overstretched. If the force applied to the knee is greater, the ligament will rupture. Case Report: The patient is a 30-year-old male who has a ruptured right MCL. He had intraoperative surgery 1 day after his injury for reconstruction. After two weeks, the patient returned to the physiotherapy clinic, where he had difficulties bending and straightening his knee, the quadriceps’ muscle strength appeared to decrease, and he had difficulty in walking. Rehabilitation had been done twice a week and included activities to facilitate the improvement of joint range of motion and muscle strength. Conclusion: The present case concluded that the training program provided can enhance knee joint range of motion following MCL surgery. The findings of this case pointed to the necessity for bigger patient groups to be studied with long-term examination of the safety and efficacy for the MCL’s exercise program.